Symbolic and Direct Forms of Violence Against Women in Turkey: The Phenomenon of Honour and Honour Killings - Hamzaoğlu, Mehtap; Konuralp, Emrah (The Bulletin of Legal Medicine, 2019)
There are various processes in daily life, such as invisible violence, structural, symbolic or normalised violence, which sustain the domination of one group against another. Pierre Bourdieu, from the analysis of power and domination and their social reproduction in modern societies, introduced the concept of symbolic power and violence. Symbolic power is the power to impose on the minds the idea of ​​world and social order and the social divisions based on race, religion, ethnicity or gender are legitimate and natural. Symbolic violence is realized through cognitive structures, which are our legitimate and natural assumptions, perception, thought and action frames shared by all members of our social world. Thus, symbolic violence encompasses all acts of domination and subjugation and hierarchies, which are also acts of cognition and recognition. The domination of women was realized by the establishment of a patriarchal society and state order. Without resorting to direct violence, it is seen that the codes related to the social world play an active role in sustaining symbolic violence against women, symbolic patriarchal power and domination through common perception frameworks such as education system and religion. In this article, the anthropological and sociological development of the phenomenon of honour as a form of symbolic violence normalizing the sexual control of women, and honour killings as a form of direct violence against women in the context of Turkey are examined.
Keywords: honour; honour killings; violence against women; smybolic violence